Alcohol and HIV Sexual Risk Behaviors among Injection Drug Users - Arasteh, Kamyar (2008)
We analyzed data from 6,341 injection drug users (IDUs) entering detoxification or methadone maintenance treatment in New York City between 1990 and 2004 to test the hypothesis that alcohol use and intoxication is associated with increased HIV sexual risk behaviors. Two types of associations were assessed: 1) a global association (i.e., the relationship between HIV sexual risk behaviors during the six months prior to the interview and at-risk drinking in that period, defined as more than 14 drinks per week for males or 7 drinks per week for females), and 2) an event-specific association (i.e., the relationship between HIV sexual risk behaviors during the most recent sex episode and alcohol intoxication during that episode). Sexual risk behaviors included multiple sex partners and engaging in unprotected sex. After adjusting for the effects of other variables, at-risk-drinkers were more likely to report multiple sex partners and engaging in unprotected sex with casual sex partners (both global associations). IDUs who reported both they and their casual partners were intoxicated during the most recent sex episode were more likely to engage in unprotected sex (an event-specific association). We also observed two significant interactions. Among IDUs who did not inject cocaine, moderate-drinkers were more likely to report multiple partners. Among self-reported HIV seropositive IDUs, when both primary partners were intoxicated during the most recent sex episode they were more likely to engage in unprotected sex. These observations indicate both global and event-specific associations of alcohol and HIV sexual-risk behaviors.